Antitumor activity of nivolumab on hemodialysis after renal allograft rejection. Issue 1 (December 2016) - Ong, Michael; Ibrahim, Andrea; Bourassa-Blanchette, Samuel; Canil, Christina; Fairhead, Todd; Knoll, Greg
Abstract Background Nivolumab (Opdivo™) is a novel IgG4 subclass programmed death-1 (PD-1) inhibiting antibody that has demonstrated breakthrough-designation anti-tumor activity. To date, clinical trials of nivolumab and other checkpoint inhibitors have generally excluded patients with solid organ transplantation and patients with concurrent immunosuppression. However, organ transplant recipients are at high-risk of development of malignancy as a result of suppressed immune surveillance of cancer. Case presentation We illustrate the outcomes of a 63 year-old type I diabetic female patient who developed pulmonary metastatic, BRAF wild-type cutaneous melanoma 10 years after renal transplantation. After downward titration of the patient's immunosuppressive medications and extensive multidisciplinary review, she was treated with nivolumab in the first-line setting. Within 1 week of administration, the patient experienced acute renal allograft rejection, renal failure and concurrent diabetic ketoacidosis due to steroid therapy. Allograft function did not return, but patient made a full clinical recovery after being placed on hemodialysis. Subsequently, the patient had clinical disease progression off therapy and required re-challenge with nivolumab on hemodialysis, resulting in ongoing clinical and radiographic response. Conclusions This case illustrates multiple practical challenges and dangers of administering anti-PD1 immune checkpoint inhibitors to patients with solid-organ transplantation including need for titration of immunosuppressive medications, risks of allograft rejection, and treatment during hemodialysis.